Downregulation of thrombomodulin contributes to ischemia‐reperfusion injury in mice with steatotic liver. Issue 9 (9th July 2022) - Yamaguchi, Megumi; Tashiro, Hirotaka; Kuroda, Shintaro; Okimoto, Sho; Kobayashi, Tsuyoshi; Hinoi, Takao; Ohdan, Hideki
Abstract: Aim: Ischemia‐reperfusion (IR) injury is one of the most critical complications commonly associated with liver surgery, including liver transplantation. Steatotic livers are particularly vulnerable to IR injury. However, the underlying mechanisms of this increased susceptibility have not fully been understood. In the present study, we used heterogeneous thrombomodulin (TM)‐knockout (KO) ( TM +/− ) mice, which express about 50% functional activity of TM as compared with wild type, to investigate whether dysregulation of TM enhances IR injury in steatotic livers. Methods: Steatotic livers were induced using choline‐deficient diets (CDD) in mice. The biological activity of TM was assessed using the productivity of protein C. Susceptibility to IR injury was compared between steatotic livers and non‐steatotic livers and also assessed in TM‐KO mice. We investigated whether recombinant TM (rTM) and the lectin‐like domain of TM (rTM‐D1) ameliorated IR injury in steatotic livers. Results: Protein C activity was significantly decreased to less than 20% in CDD‐fed mice compared with mice with non‐steatotic livers. Steatotic livers showed exaggerated IR injury compared with non‐steatotic livers. Recombinant TM (rTM) and the lectin‐like domain of TM (rTM‐D1), which has anti‐inflammatory effects, ameliorated IR injury in steatotic livers. TM +/− mice showed increased susceptibility to IR injury, and rTM ameliorated the increased IR injury in TM +/− mice. Conclusion: We conclude that downregulation of TM increases susceptibility to hepatic IR injury in steatotic livers and that rTM ameliorates hepatic IR injury through anti‐inflammatory action.